Conservation programs in the 2018 farm bill - Lichtenberg, Erik (2018)
Erik Lichtenberg BOOK LAUNCH Agricultural Policy in Disarray: Reforming the Farm Bill Co-Hosted by IFPRI and American Enterprise Institute DEC 12, 2018 - 12:15 PM TO 01:45 PM EST